La France en quête de confiance : la construction des émotions dans les voeux des hommes politiques pour la nouvelle année - Kostro, Monika (Studia Romanica Posnaniensia, 2015)
With the development of political communication over the Internet, a growing number of the French politicians are posting online their New Year’s Messages, which have been so far a genre of political discourse reserved for the President. These speeches have a similar pattern, which apart from wishes include an evaluation of the passing year and plans for the future. This is so, because the New Year’s Messages have primarily a persuasive function, and serve the purpose of strengthening the addressees’ group identity by reminding them of common values. However, while the President’s speech is strongly ritualized and emotionally balanced – as it is addressed to the whole nation – the online speeches are not subject to certain conventions, which allows the politicians to adjust the tone of their speech to the expectations of their supporters. Therefore a whole range of feelings is applied – from the fear of France falling, to national pride – depending on the political aims which are to be achieved. This article makes an attempt at answering the question in which way these emotions are constructed within the speeches, and which persuasive function they embody. The author adopts the perspective of argument analysis in discourse (Amossy, 2000; Plantin, 2011), which perceives emotions as a rhetoric means (pathos) whose aim is to influence the addressee.